Pediatric death audit with special emphasis on autopsy at the University of Uyo Teaching Hospital, Uyo, Nigeria: a 6-year review - IJEZIE Echey; OKPOKOWURUK, Frances Sam; NWAFOR, Chukwuemeka Charles (Pediatric Review: International Journal of Pediatric Research, 2015)
Background and Objectives: Paediatric autopsies are useful in the establishment of diagnosis, quality assurance and research. They are relevant in guiding genetic counseling and helping families that are grieving. Despite these uses and applications, autopsy rates have declined globally. This study was undertaken to identify the autopsy rate in the Department of Paediatrics at the University of Uyo Teaching Hospital (UUTH), Uyo, Nigeria.Materials and Methods: The current report is a descriptive, cross-sectional and retrospective review of all the deaths among the hospitalized children from 1st January 2009 to 31st December 2014. Relevant information was extracted from case files of all in-patient deaths during the period under review.Results: A total of 772 paediatric deaths were recorded during the period under review, of which 453 (58.7%) were males and 319 (41.3%) were females. Two hundred and twelve [212 (37.5%)] deaths occurred within 24 hours of admission. No autopsy was conducted (0%) on any of the cases.Conclusion: Despite the importance, paediatric autopsies are not routinely performed in this centre, and in many others. This should not be the case. Paediatric autopsy rates can be improved by making consistent autopsy requests by the attending clinicians. Advocacy and enlightenment campaigns should be conducted at facility and community levels to educate everyone concerned about the benefits of paediatric autopsies.